Family tree generator (FTGen) - Noryasmin, Ahmad Khashiri (2010)
This thesis explained about the" family tree and family tree generator. In managing a family or create and generate a family, it is very difficult to manage by individual if still using the traditional way. In the era of technology, recently most of the data is display in digital content. Few years ago, the family tree was created manually. This need more time and cost because needed to draw and write on a large paper if there are big family and might be only the name and picture can put at that paper. Recently, everything come easy, fast and save cost. In digital format, family members data can be edit and manipulate easily. In this thesis, a model of system for generating family tree called Family Tree Generator (FTGen) are discussed and developed. This system is used to replace the traditional operations since it can improve and enhances the workflow in managing a family. Suitable software development process models were used in order to produce efficient and effective end product which based on researched result. The analysis comprises of studied on methodologies, tools, requirements and case study. At the end, there will be a computerized family tree system which follows the requirement specification and operates as expectations developed.